“The Turn of the Screw”: Secrets of an Atmospheric Text (Students’ roundtable discussion. Lomonosov Moscow State University, Faculty of Philology, December 11, 2024) - - (Литература двух Америк, 2025)
The Department of Discourse and Communication Studies of the Faculty of Philology (Lomonosov Moscow State University) regularly holds round tables for advanced graduate students to discuss classic literary works and their adaptations. In December 2024 a roundtable discussion “The Secret of Atmospheric Prose, or ‘The Turn of the Screw’ by Henry James” was held, which was attended by both researchers of the American classic’s work and students. Henry James’s “The Turn of the Screw” (1898) is perhaps the most famous ghost story in world literature. James’s story, like its numerous adaptations for the screen and the stage (film, TV series, and opera), has a powerful atmospheric effect: although nothing happens, we are given a sense of mystery, gradually increasing tension, lurking danger, and horror. The participants of the round table have engaged with the following topics: how an atmospheric text holds the reader’s imagination; how the experience of encountering the unknown, the mysterious, the dangerous is shaped and conveyed in it; what elements of the film language help design the atmosphere in film adaptations, and also — whether the work of the viewer’s imagination is similar or different from the work of the reader’s imagination.